2016
DOI: 10.1515/amm-2016-0270
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Investigation of Thermal and Wear Properties of Zinc Novel Coatings Reinforced with Nano-Al2O3 and Cr2O3 Particles

Abstract: The study of the thermal, wear and corrosion properties of developed nanocomposite coatings of Zn-Al2O3 and Zn-Cr2O3 was carried out. The coatings were produced by electrodeposition technique from chloride acidic bath. Laboratory tube furnace was used for the thermal analysis. The wear test was performed using CETR tribo-tester dry reciprocating tester. The hardness properties were investigated using diamond base Dura microhardness tester. Scanning electron microscope (SEM) affixed with energy dispersive spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The result of the adhesion, smearing was also visible on the counterface ball surface (Figure 7(b)). It has been noted that the presence of Zn- Al 2 O 3 coating reduces the friction coefficient of mild steel substrates [19,20]. They showed that alumina particles in the Zn matrix provide a lubricating effect to the matrix, reducing the direct contact of the abrasive ball with the metal matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The result of the adhesion, smearing was also visible on the counterface ball surface (Figure 7(b)). It has been noted that the presence of Zn- Al 2 O 3 coating reduces the friction coefficient of mild steel substrates [19,20]. They showed that alumina particles in the Zn matrix provide a lubricating effect to the matrix, reducing the direct contact of the abrasive ball with the metal matrix.…”
Section: Resultsmentioning
confidence: 99%
“…This results in a uniform distribution of reinforcements within the matrix, enhancing mechanical properties such as strength, stiffness, and fatigue resistance.Moreover, FSP can refine the grain structure of the aluminum matrix, leading to improved mechanical properties and better control over material properties [22]. This is particularly beneficial for aluminum composites, as it enhances their performance in demanding applications such as aerospace, automotive, and marine industries.Furthermore, FSP allows for precise control over the processing parameters, including tool rotation speed, traverse speed, and applied pressure, enabling tailored microstructural modifications to meet specific performance requirements [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%